BAHASA, PIKIRAN, DAN REALITAS MERUPAKAN KESATUAN SISTEM YANG TIDAK DAPAT DIPISAHKAN - Setyonegoro, Agus (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2014)
This  article  aim  to  explain  "language,  mind,  and  reality  is  unity  of  inseparable system".  For  the  purpose,  there  is  two  the  fundamental  elaborated  at  this  article, that is (1) reality and function of language and (2) the relation of mind, language, and  reality.  Description  firstly  include  (a)  linguistic  reality  and  (b)  function  of language.  Including  second  description  (a)  the  relation  of  mind,  language,  and reality and (b) clarity thinks and having language.Key Words: language, mind, reality